Burden of illness among Medicare and non-Medicare US populations with acquired thrombotic thrombocytopenic purpura. (1st January 2021) - Pollissard, Laurence; Shah, Anne; Punekar, Rajeshwari S.; Petrilla, Allison; Pham, Huy P.
Abstract: Background: Acquired thrombotic thrombocytopenic purpura (aTTP) is a rare hematologic disorder that can lead to serious life-threatening medical complications. Objective: The aim of this study was to describe aTTP-related hospital resource utilization, cost, complications, and overall survival among US Medicare and non-Medicare populations following aTTP episodes prior to the US approval of caplacizumab. Methods: This retrospective study utilized administrative claims data for Medicare Fee-for-Service (FFS) beneficiaries (100% sample) and a sample of commercial, managed Medicaid [MM], Medicare Advantage [MA] plan members from the Inovalon MORE 2 Registry. aTTP patients ages 18+ were identified between 2010 and 2018 using a published validated algorithm: ≥1 hospitalization for thrombotic microangiopathy + therapeutic plasma exchange (TPE). 2, 279 patients were identified; 65.2% were enrolled in Medicare FFS, 13.6% in commercial, 15.7% in MM, and 5.4% in MA. Mean hospitalization days for aTTP index episode ranged between 12 and 17 days; ∼60% of patients required intensive care. Mean payments for index hospitalization varied by payer [Medicare FFS: $29, 024; MA: $12, 860; commercial: $9, 996 and MM: $10, 470]. Among FFS patients, 15.7% died during initial hospitalization and 21.0% died within first 30 days of the event. During follow-up, 11.6–19.6% experienced aTTP-related exacerbation. Incidence rate of relapse and complications per 100 person-years was 5.6 [Medicare FFS: 3.6; MA: 8.7; commercial: 10.4 and MM: 14.7] and 16.7 [FFS: 15.5; MA: 20.5; commercial: 21.7 and MM: 19.1], respectively. Among Medicare patients with and without aTTP, mortality risk was 2.9 (95 % CI: 2.4–3.4) times higher for aTTP vs. non-aTTP patients. Conclusion: This is the first real-world study evaluating burden of illness among aTTP patients in the US across payer types. Despite being treated with TPE, patients with aTTP have lower survival rates in comparison to a matched cohort without aTTP. These findings highlight the need for more effective and novel therapies to reduce disease burden for this population. Key points: In US Medicare and managed care populations with aTTP between 2010 and 2018, aTTP can lead to significant utilization of ICU services due to clinical complications, and/or relapse following hospital discharge. Despite treatment with therapeutic plasma exchange, acute mortality remains high (15.7%) indicating the need for more effective and novel treatments.